BBL - La collection d'ArT. - Adriaens-Pannier, Anne; Callewaert, Bernadette; D'Haeye, Bernadette; De Peuter, Patricia; Gassner, Hubertus; Gildemyn, Marie-Pascale; Kaufmann, Marie-Amélie; Lorent, Claude; Navez, Delphine; Pas, Johan; Petre, Anne; Tilmant, Michel; et al. (Brussel : BBL (Bank Brussel Lambert), 1997)
Adami, Valerio ; Albers, Josef ; Alechinsky, Pierre ; Amado, Jean ; Arroyo, Eduardo ; Art & Language ; Baselitz, Georg ; van den Berghe, Frits ; Berrocal, Miguel ; Blais, Jean-Charles ; Boetti, Alighiero ; Bogart, Bram ; Brusselmans, Jean ; Buren, Daniel ; Bury, Pol ; Buthe, Michael ; Calder, Alexander ; Cardenas, Agustin ; Caulfield, Patrick ; César ; Charlton, Alan ; Chia, Sandro ; Collignon, Georges ; Cragg, Tony (Anthony) ; Darboven, Hanne ; Dekkers, Ad ; Delahaut, Jo ; Demarco, Hugo ; Denmark ; Dufo, Alain ; Vanden Eeckhoudt, Jean ; van Elk, Ger ; Engels, Pieter ; Fabre, Jan ; Fermariello, Sergio ; Filippini, Alessandro ; Fisher, Joel ; Fromanger, Gérard ; Gac, Jean Le ; Gäfgen, Wolfgang ; Garouste, Gérard ; Gentils, Vic ; Gilbert & George ; Green, Alan ; Hall, Nigel ; Halley, Peter ; Hiquily, Philippe ; Van Hoeydonck, Paul ; Indiana, Robert ; Jenkins, Paul ; Kelly, Ellsworth ; Kirkeby, Per ; Koch, Ödön ; Kushner, Robert ; Lafontaine, Marie-Jo ; Lasker, Jonathan ; Leblanc, Walter ; LeWitt, Sol ; Lichtenstein, Roy ; Luethi, Rolf ; Lüpertz, Markus ; Luyten, Mark ; McCollum, Allan ; Middendorf, Helmut ; Moore, Henry ; Mortier, Antoine ; Müller, Robert ; Mullican, Matt ; Muñoz, Juan ; Nash, David ; Opie, Julian ; Oppenheim, Dennis ; Orozco, Gabriel ; Paladino, Mimmo ; Paolini, Giulio ; Paolozzi, Eduardo ; Parc, Julio Le ; Penck, A.R. ; Pepper, Beverly ; Permeke, Constant ; Pistoletto, Michelangelo ; Poirier, Anne & Patrick ; Pomodoro, Arnaldo ; Rauschenberg, Robert ; Riley, Bridget ; Ruff, Thomas ; De Smet, Gustave ; Steir, Pat ; Stella, Frank ; Suvero, Mark di ; Tremlett, David ; Tytgat, Edgard ; Vandenberg, Philippe ; Vasarely, Victor ; Vercruysse, Jan ; Verheyen, Jef ; Visser, Carel ; Voss, Jan ; Warhol, Andy ; Wotruba, Fritz ; Wouters, Rik ; Zush
biog., tent., bibliog. per kunstenaar
tent. georganiseerd door de BBL p. 285-290, bibliog. p. 291, auteurs p. 292
Frans & Nederlands & Engels & Duits
boek